Efficacy and tolerability of a fixed-dose moxifloxacin – dexamethasone formulation for topical prophylaxis in LASIK: a comparative, double-masked clinical trial - Mauro Campos (Dove Medical Press, 2008)
Mauro Campos, Mariana Ávila, Anelise Wallau, Cristina Muccioli, Ana Luisa Höfling-Lima, Rubens Belfort JrDepartment of Ophthalmology, Escola Paulista de Medicina, Universidade Federal de São Paulo, São Paulo, BrazilPurpose: To compare the efficacy and tolerability of a fixed-dose combination of 0.5% moxifloxacin and 0.1% dexamethasone formulation (MFLX/DEX) vs conventional dosing with both agents dosed separately for prophylaxis after laser-assisted in situ keratomileusis (LASIK).Methods: A prospective, randomized, double-masked, parallel-group study of 64 patients undergoing bilateral LASIK. Patients received either combined MFLX/DEX and placebo or moxifloxacin and dexamethasone dosed separately in both eyes. Baseline and postoperative assessments were made on surgery days –2, 1, 3, 8, and 15 and consisted of uncorrected visual acuity (UCVA), intraocular pressure (IOP), severity of inflammation, endothelial cell loss, ocular pain, burning, and itching sensation. The posterior segment was evaluated at the screening and exit visits.Results: Of the 64 patients treated, 7 eyes did not meet the inclusion criteria and were excluded from the analysis. No ocular infection or persistent inflammation developed. Postoperatively there were no statistical differences between treatments for most parameters measured. More eyes in the combined MFLX/DEX group reported pruritus and burning post operatively; however, differences were also observed at baseline.Conclusion: Topical prophylaxis with MFLX/DEX eye drops was well tolerated and is therapeutically equivalent to conventional dosing with moxifloxacin and dexamethasone from individual bottles.Keywords: moxifloxacin, dexamethasone, LASIK, prophylaxis